Real-World Efficacy and Safety of Anti-PD-1 Antibody Plus Apatinib and Temozolomide for Advanced Acral Melanoma - Zhang J; Tian H; Mao L; Li C; Wei X; Gu J; Wang X; Zhou L; Lian B; Tang B; Yan X; Li S; et al. (Cancer Management and Research)
Jiaran Zhang,1,* Huichun Tian,1,* Lili Mao,1 Caili Li,1 Xiaoting Wei,1 Junjie Gu,1 Xuan Wang,1 Li Zhou,2 Bin Lian,1 Bixia Tang,1 Xieqiao Yan,2 Siming Li,2 Chuanliang Cui,1 Zhihong Chi,1 Xinan Sheng,2 Jun Guo,1 Lu Si1 1Department of Melanoma and Sarcoma, Peking University Cancer Hospital & Institute, Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), Beijing, 100142, People’s Republic of China; 2Department of Genitourinary Oncology, Peking University Cancer Hospital & Institute, Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), Beijing, 100142, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lu Si, Peking University Cancer Hospital & Institute, Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), 52# Fucheng Road, Haidian District, Beijing, 100142, People’s Republic of China, Email silu15_silu@126.comPurpose: The combination of programmed cell death-1 (PD-1) blockade camrelizumab plus apatinib (an antiangiogenic agent) and temozolomide has displayed promising therapeutic effects in patients with advanced acral melanoma (AM) in a non-randomized Phase II clinical trial (NCT04397770). The aim of this retrospective study was to evaluate the efficacy and safety of the triplet regimen for advanced AM in the real-world setting.Methods: The data of patients with advanced AM who received anti-PD-1 antibody plus apatinib and temozolomide at Peking University Cancer Hospital and Institute between September 2019 and December 2023 were analyzed. The primary endpoint was the overall response rate (ORR). The secondary endpoints included progression-free survival (PFS), overall survival (OS), disease control rate (DCR), duration of response (DOR), and treatment-related adverse events (TRAEs).Results: Overall, 250 patients were eligible for the analysis. The ORR was 38.1% and the DCR was 92.2%. The median PFS, OS, and DOR were 8.5, 18.0, and 13.2 months, respectively. When used as first-line treatment, the ORR was 48.1%, the median PFS was 12.0 months, and the median OS was 24.8 months. The number of lines of therapy (≥ 2 lines), elevated lactate dehydrogenase, and presence of brain or liver metastasis were negative predictors of survival. Overall, 92.4% and 45.2% of the patients experienced any-grade and grade 3– 4 TRAEs, respectively.Conclusion: This study provides real-world evidence that support the effectiveness and safety of combined anti-PD-1 antibody, apatinib and temozolomide for treating advanced AM, demonstrating a considerable ORR and prolonged survival, as well as acceptable tolerability.Keywords: acral melanoma, PD-1, anti-angiogenesis, apatinib, camrelizumab, temozolomide, objective response rate